2016
DOI: 10.1371/journal.pone.0144485
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Urbanism and Information Consumption on Political Dimensions of Social Capital: Exploratory Study of the Localities Adjacent to the Core City from Brașov Metropolitan Area, Romania

Abstract: BackgroundThe last two decades have seen a growing trend towards the research of voting behavior in post-communist countries. Urban sociology theorists state that not only space structures influence political participation, but also space structures are changing under the influence of global, local, and individual factors. The growing role played by information in the globalised world has accelerated the paradigm shift in urban sociology: from central place model (based on urban-rural distinction and on monoce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Social support is a wide concept and it is important for people in general and women in particular to receive social support in any area of their life. In this regard, previous studies (Rezeanu et al, 2016) have shown that, as the distance to the city centre increases, people's access to public services decreases. Thus, compared to women who live in the city centre, it is possible for women living in the suburban area to feel less social support, due to the lack of access to public services too.…”
Section: Introductory Aspects Regarding Postpartum and Body Imagementioning
confidence: 89%
“…Social support is a wide concept and it is important for people in general and women in particular to receive social support in any area of their life. In this regard, previous studies (Rezeanu et al, 2016) have shown that, as the distance to the city centre increases, people's access to public services decreases. Thus, compared to women who live in the city centre, it is possible for women living in the suburban area to feel less social support, due to the lack of access to public services too.…”
Section: Introductory Aspects Regarding Postpartum and Body Imagementioning
confidence: 89%
“…Castells, M. [3] consider growth of the Network Society; Charlesworth, H. researched the Public/Private Distinction and the Right to Development in International Law; Gerber, J.-D., Bandi, Tanner, M. [4] studied the Role of Alpine Development Regimes in the Development of Second Homes: Preliminary Lessons from Switzerland; Gille, F., Scalvinoni, B. [5] examined local Territorial Issues of Cross-Border Workers: The Different Examples of Thionville and Forbach; Jones, T, Newburn, T [6] analyzed comparative Criminal Justice Policy-Making in the United States and the United Kingdom: The Case of Private Prisons; Nelles, J., Durand, F. [7] examined political Rescaling and Metropolitan Governance in Cross-Border Regions: Comparing the Cross-Border Metropolitan Areas of Lille and Luxembourg, Rezeanu; C.-I., Briciu, A., Briciu, V., Repanovici, A., Coman, C. [8] researched the Influence of Urbanism and Information Consumption on Political Dimensions of Social Capital: Exploratory Study of the Localities Adjacent to the Core City from Brașov Metropolitan Area, Romania. However, the topic 'Territory as a feature of state in terms of modern public relations development ' has not yet been studied.…”
Section: Literature Reviewmentioning
confidence: 99%
“…He tends to most value comfortable settings for living and work. According to the opinion of a number of researches, such tendencies cause the appearance of polycentric spatial structures [8], which are not cities, but on which life is constantly evolving due to the fact that they absorb adjacent territories to form large agglomerations that drive economic growth of the whole region.…”
Section: E "Mega-regions" and The Territory Of A Sovereign Statementioning
confidence: 99%
“…One of the factors that decisively influences the quality of road traffic, therefore, implicitly, the risk in traffic, is the public road network. Thus, in the context of the urban and rural environment, a previous study found that people who live further from the center of the city have access to more public services than people who live closer (Rezeanu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%